Expression of Dopamine Receptors in the Lateral Hypothalamic Nucleus and Their Potential Regulation of Gastric Motility in Rats With Lesions of Bilateral Substantia Nigra - Yang, Yan-Li; Ran, Xue-Rui; Li, Yong; Zhou, Li; Zheng, Li-Fei; Han, Yu; Cai, Qing-Qing; Wang, Zhi-Yong; Zhu, Jin-Xia (Frontiers in Neuroscience, 2019)
Most Parkinson’s Disease (PD) patients experience gastrointestinal (GI) dysfunction especially the gastroparesis, but its underlying mechanism is not clear. We have previously demonstrated that the neurons in the substantia nigra (SN) project to the lateral hypothalamic nucleus (LH) and the dorsal motor nucleus of vagus (DMV) receives the neural projection from LH by the means of anterograde and retrograde neural tracing technology. Orexin A (OXA) is predominately expressed in the LH. It has been reported that OXA can alter the gastric motility through the orexin receptor 1 (OX1R) in DMV. We speculated that this SN-LH-DMV pathway could modulate the motility of stomach because of the important role of LH and DMV in the regulation of gastric motility. However, the distribution and expression of dopamine receptors (DR) in the LH is unknown. In the present study, using a double-labeling immunofluorescence technique combined with confocal microscopy, we significantly extend our understanding of the SN-LH-DMV pathway by showing that (1) a considerable quantity of dopamine receptor 1 and 2 (D1 and D2) was expressed in the LH as well as the OX1R was expressed in the DMV; (2) Nearly all of the D1-immuoreactve (IR) neurons were also OXA-positive while only a few neurons express both D2 and OXA in the LH, and the DR-positive neurons were surrounded by the dopaminergic neural fibers; In the DMV, OX1R were colocalized with choline acetyltransferase (ChAT)-labeled motor neurons; (3) When the gastroparesis was induced by the destruction of dopaminergic neurons in the SN, the decreased expression of D1 and OXA was observed in the LH as well as the reduced OX1R and ChAT expression in the DMV. These findings suggest that SN might regulate the function of OXA-positive neurons via D1 receptor, which then affect the motor neurons in the DMV through OX1R. If the SN is damaged the vagal pathway would be affected, which may lead to gastric dysfunction. The present study raises the possibility that the SN-LH-DMV pathway can regulate the movement of stomach.